(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The teachings and writings of John Dewey, an American philosopher and educator, offer insightful influences on contemporary education, not only in the United States but also worldwide. His philosophy of education, commonly referred to as Pragmatism, focused on learning by doing as an alternative to rote knowledge and strict teaching. The purpose of this study is to investigate the extent to which this philosophical thought is implemented in Jordanian public schools according to Jordanian teachers. Both quantitative and qualitative methods were employed in this study. The findings reveal that Jordanian teachers believe Pragmatism is implemented in Jordan to a moderate degree. This theory of learning was connected to a strategy of teaching and, most importantly, his personal philosophy. His philosophy required an understanding of what constitutes a good society and the right way of life, and an acknowledgment that change is a condition of life. He emphasized that the nature of wisdom, understanding, and intelligence is fundamentally moral. Even though he is no longer widely known